LPS injection reprograms the expression and the 3′ UTR of a CAP gene by alternative polyadenylation and the formation of a GAIT element in Ciona intestinalis. (September 2016) - Vizzini, Aiti; Bonura, Angela; Longo, Valeria; Sanfratello, Maria Antonietta; Parrinello, Daniela; Cammarata, Matteo; Colombo, Paolo
Highlights: LPS injection reprograms the expression of a CAP gene in Ciona intestinalis. LPS challenge induces an APA site in the first intron of a CAP gene. LPS induced APA causes the appearances of a GAIT element in 3′ UTR of a CAP gene. Abstract: The diversification of cellular functions is one of the major characteristics of multicellular organisms which allow cells to modulate their gene expression, leading to the formation of transcripts and proteins with different functions and concentrations in response to different stimuli. CAP genes represent a widespread family of proteins belonging to the cysteine-rich secretory protein, antigen 5 and pathogenesis-related 1 superfamily which, it has been proposed, play key roles in the infection process and the modulation of immune responses in host animals. The ascidian Ciona intestinalis represents a group of proto-chordates with an exclusively innate immune system that has been widely studied in the field of comparative and developmental immunology. Using this biological system, we describe the identification of a novel APA mechanism by which an intronic polyadenylation signal is activated by LPS injection, leading to the formation of a shorter CAP mRNA capable of expressing the first CAP exon plus 19 amino acid residues whose sequence is contained within the first intron of the annotated gene. Furthermore, such an APA event causes the expression of a translational controlling cis -acting GAIT element which is not present in the previously isolated CAP isoform and identified in the 3′-UTR of other immune-related genes, suggesting an intriguing scenario in which both transcriptional and post-transcriptional control mechanisms are involved in the activation of the CAP gene during inflammatory response in C. intestinalis .